Integrated transcriptome, metabolome and phytohormone analysis reveals developmental differences between the first and secondary flowering in Castanea mollissima - Qin, Cai; Du, Tingting; Zhang, Ruiyu; Wang, Qiujie; Liu, Yang; Wang, Tianyi; Cao, Hongyan; Bai, Qian; Zhang, Yu; Su, Shuchai (Frontiers in Plant Science, 2023)
Chestnut (Castanea mollissima BL.) is an important woody grain and flower formation has an important impact on fruit yield and quality. Some chestnut species in northern China have the characteristic of re-flowering in the late summer of the year. On the one hand, the second flowering will consume a lot of nutrients in the tree, weakening the tree and thus affecting flowering in the following year. On the other hand, the number of female flowers on a single fruiting branch of second flowering is significantly higher than that of first flowering, which can bear fruit in bunches, and therefore can be used as an important material to study the sex differentiation of chestnut. In this study, the transcriptome, metabolome and phytohormones were determined for male and female flowers of chestnut in spring and late summer. We wanted to understand the developmental differences between secondary and first flowering in chestnut. We will analyze the reasons why the number of female flowers is higher in secondary flowering than in first flowering and find ways to increase the number of female flowers or decrease the number of male flowers in chestnut. By analyzing the development of male and female flowers at different developmental stages, the transcriptome revealed that EREBP-like mainly affected the development of secondary female flowers and HSP20 mainly affected the development of secondary male flowers. KEGG enrichment analysis showed that 147 co-regulated differentially significant genes were mainly enriched in circadian rhythm-plant, carotenoid biosynthesis, phenylpropanoid biosynthesis, and plant hormone signal transduction. The metabolome showed that the main differential metabolites between female flowers were flavonoids and phenolic acids, while the main differential metabolites between male flowers were lipids, flavonoids and phenolic acids. These genes and metabolites were positively correlated with secondary flower formation. The analysis of phytohormones showed that abscisic acid and salicylic acid seemed to be negatively correlated with secondary flower formation. Meanwhile, MYB305, a candidate gene for sex differentiation in chestnut, promoted the synthesis of flavonoid substances and thus increased the number of female flowers. This study has important practical implications for improving the yield and quality of chestnut.